ANALISIS LAPORAN KEUANGAN SEBAGAI SALAH SATU ALAT UNTUK MENILAI KINERJA KOPERASI SIMPAN PINJAM (KSP) “SEKAR WANGI” DI CAKRANEGARA - Sri Ayu Febrianti; Saepul Pahmi; Suandi, Suandi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2021)
This study aims to determine the financial performance so that it can be seen the conditions and achievements that have been achieved by the Savings and Loans Cooperative (KSP) "Sekar Wangi" in Cakranegara. The type of research used in this research is descriptive research. Data collection techniques used are observation, interviews, and documentation. Based on the discussion and data analysis, it can be concluded that by using comparative analysis of financial statements, it can be said that the business run by KSP "Sekar Wangi" Cakranegara has increased, and based on calculations using financial ratios, it can be said that the management performance of KSP "Sekar Wangi" Cakranegara not optimal and need to be improved.